الصدمة الإنتانية (Latakia University Journal -Medical Sciences Series, 2019)
درست الصدمة الإنتانية عند 33 مريضا" (13 ذكراً) في مشفى الأسد الجامعي في اللاذقية خلال الفترة بين 1/3 /2005 حتى 1/7 /2006 . لوحظ ازدياد معدل حدوث الصدمة الإنتانية بازدياد العمر حيث حدثت الصدمة الإنتانية عند 27 مريضاً (81.81% ) ممن تجاوزوا سن الخمسين . أهم عوامل الخطورة المسجلة كانت العمر اكبر من خمسين 27 مريضاً (81.81% ) – الداء السكري عند 18 مريضاً (54.54% ) ثم السرطانات عند 6 مرضى (18.18 % ) فالجراحات والإجراءات الباضعة عند 5 مرضى (15.15 % ) . كانت  الإنتانات الرئوية المصدر الأول للإنتان 10 مرضى (30.30 % ) ثم الجهاز الصفراوي 5 مرضى (15.15 % ) و البولي 5 مرضى (15.15 % ) ثم الأجهزة الأخرى . كان زرع الدم ايجابياً عند 10 مرضى (30.30 % ) ، وكان الزرع لعينات مأخوذة من مصدر الإنتان المتوقع ايجابياً عند 9 مرضى (27.27 % ) . تطورت الإصابة إلى الوفاة عند 31 مريضاً (93.93 % ) . 33 adult patients (13 males) with septic shock were studied at Al-Assad University Hospital in Lattakia from 1/3/2005 to 1/7/2006. The incidence of septic shock was found to increase with age, it occurred in 27 patients (81.81%) over 50 years of age.     The most important risk factors were: age over 50 years in 27 patients (81.81 %)-diabetes mellitus in18 patients (54.54 %) – cancers in 6 patients (18.18 %) - surgery and invasive procedure in  5 patients (15.15 %). The source of sepsis was: pulmonary sepsis in 10 patients (30.30 %) - biliary system in 5 patients (15.15 %) – urinary system in 5 patients (15.15 %),  followed by the other systems .Blood culture was positive in 10 patients (30.30 %) and the culture of samples taken from the suspected source of sepsis was positive in 9 patients (27.27 %). Mortality rate was very high in 31 patients (93.93%).